Інтегрований профіль експресії осі ММР-ТІМР-мікроРНК у клітинах раку молочної залози різного молекулярного підтипу - Lukianova, N.; Burda, T.; Mushii, O.; Zadvornyi, T.; Pavlova, A.; Chekhun, V. (PH Akademperiodyka, 2025)
Background. Invasion and metastasis of breast cancer (BC) critically depend on extracellular matrix (ECM) remodeling, regulated by matrix metalloproteinases (MMPs) and their endogenous tissue inhibitors (TIMPs). The dysregulation of the MMP-TIMP axis, together with the post-transcriptional control by microRNAs (miRNAs), contributes to the aggressive phenotype of BC. Materials and Methods. The expression of collagenases (MMP-1, MMP-8, MMP-13), gelatinases (MMP-2, MMP-9), TIMP1—4, and selected regulatory miRNAs (miR-34a-5p, miR-100-5p, miR-132-3p, miR-145-5p, miR-155-5p, miR-200b-5p) was analyzed by immunocytochemistry and real-time PCR in 4 human BC cell lines representing different molecular subtypes (MCF‑ 7, T47D, MDA-MB-231, MDA-MB-468). Results. Distinct subtype-specific expression profiles were identified. At the mRNA level, the triple-negative BC cells showed the highest expression of collagenases (MMP1, MMP8, MMP13) and MMP9, whereas luminal BС cells of the MCF‑ 7 line exhibited the maximal MMP2 levels. At the protein level, collagenases predominated in the luminal BC cell lines (T47D, MCF‑ 7), while gelatinases were most abundant in MDA-MB-231. TIMP1 and TIMP3 transcripts were the highest in T47D, TIMP2 in MDA-MB-468 cells, while the TIMP3 expression in MDA-MB-231 cells was absent. miRNA profiling revealed a generally higher expression of miR-34a-5p, miR-100-5p, miR-132-3p, and miR-145-5p in the triple-negative BC cell lines, whereas MCF‑ 7 cells displayed the lowest levels except for miR-155-5p, the expression of which was maximal. The discrepancies between mRNA and protein levels suggest a miRNA-mediated post-transcriptional regulation, although not universally consistent across all MMPs. Conclusions. The study demonstrates that the MMP-TIMP-miRNA axis exhibits subtype-specific expression patterns in the BC cell lines. The observed heterogeneity highlights the importance of post-transcriptional regulation and suggests that integrated profiling of MMPs, TIMPs, and regulatory miRNAs may provide novel insights into the invasive potential of BC and identify candidate biomarkers for clinical validation.